Optimal PV Inverter Reactive Power Control and Real Power Curtailment to Improve Performance of Unbalanced Four-Wire LV Distribution Networks - Su, Xiangjing; Sherkat Masoum, Ali; Wolfs, Peter (The Institute of Electrical and Electronic Engineers (IEEE), 2014)
The rapid uptake of residential photovoltaic (PV); systems is causing serious power quality issues such as significant voltage fluctuation and unbalance that are restricting the ability of networks to accommodate further connections. Based on the latent reactive power capability and real power curtailment of singlephase inverters, this paper proposes a new comprehensive PVoperational optimization strategy to improve the performance of significantly unbalanced three-phase four-wire low voltage (LV) distribution networks with high residential PV penetrations. Amultiobjective optimal power flow (OPF) problem that can simultaneously improve voltage magnitude and balance profiles, while minimizing network losses and generation costs, is defined and thenconverted into an aggregated single-objective OPF problem using the weighted-sum method, which can be effectively solved by the global Sequential Quadratic Programming (SQP) approach withmultiple starting points in MATLAB. Detailed simulations are performed and analyzed for various operating scenarios over 24 h on a real unbalanced four-wire LV distribution network in Perth Solar City trial, Australia. Finally, smart meter readings are used to justify the validity and accuracy of the proposed optimization model and considerations on the application of the proposedPV control strategy are also presented.